FLEXIBILITY AND ADAPTABILITY OF DOMESTIC SPACE BASED ON EVERYDAY ARCHITECTURE - Redyantanu, Bramasta Putra (Ide dan Dialog Desain Indonesia (Idealog), 2023)
This paper aims to discuss the idea of forming flexible and adaptive architecture for various scenarios through the perspective of everyday architectural knowledge. The background of this study is based on the issue and phenomenon of the development of housing to be more varied than just a living space, but also various other additional functions during a pandemic. Multiple activities outside the home are now part of the domestic activities themselves. A study of a residential building design illustrates how every day operations reflect the adaptability and flexibility of domestic space. The exploration and analysis of the study object are presented through the redrawing of the space configuration along with the trajectory of daily activities. The connection between space, time, and users is described as a daily practice that has the potential to develop future design methods. The findings of this qualitative study are to see how the process of forming adaptive and flexible architecture. Domestic architecture can show the dynamics of space rather than just the static configuration visible. The findings of this study include at least three aspects, making the everyday space, using the everyday, and the configuration that is the extra ordinary. Reflections from this study show the expansion of architectural design practices that need to pay attention to the ability of space to be adaptive and flexible based on dynamic everyday life. Keywords : everyday architecture, domestic architecture, flexible adaptive architecture